2014
DOI: 10.1073/pnas.1318261111
|View full text |Cite
|
Sign up to set email alerts
|

Language universals at birth

Abstract: The evolution of human languages is driven both by primitive biases present in the human sensorimotor systems and by cultural transmission among speakers. However, whether the design of the language faculty is further shaped by linguistic biological biases remains controversial. To address this question, we used near-infrared spectroscopy to examine whether the brain activity of neonates is sensitive to a putatively universal phonological constraint. Across languages, syllables like blif are preferred to both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 39 publications
4
54
0
Order By: Relevance
“…It is also unlikely that the effects reported here are solely due to participants' phonological experience with Mandarin or with English-their second language. While our present results from adult Mandarin speakers cannot rule out the contribution of those factors, it is nonetheless interesting to note that similar sensitivity to the onset hierarchy obtains even in neonates (Gómez et al 2014). Whether the onset hierarchy is due to linguistic constraints, and whether those constraints are truly universal are questions awaiting further research.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…It is also unlikely that the effects reported here are solely due to participants' phonological experience with Mandarin or with English-their second language. While our present results from adult Mandarin speakers cannot rule out the contribution of those factors, it is nonetheless interesting to note that similar sensitivity to the onset hierarchy obtains even in neonates (Gómez et al 2014). Whether the onset hierarchy is due to linguistic constraints, and whether those constraints are truly universal are questions awaiting further research.…”
Section: Resultsmentioning
confidence: 59%
“…Contrary to the motor account, ill-formed syllables disengage the articulatory system ; and their misidentification persists even when articulatory motor system is suppressed by Transcrnial Magnetic Stimulation (Berent et al 2015). Moreover, the results obtain with speakers of various languages (English: Berent et al 2007;French: Maïonchi-Pino et al 2012;Korean: Berent et al 2008;Spanish: Berent et al 2012a, b) and despite minimal linguistic and articulatory experience-in the brains of neonates (Gómez et al 2014). These results are in line with the possibility that speakers share universal restrictions on syllable structure.…”
Section: Introductionmentioning
confidence: 97%
“…In line with this possibility, past research has shown that people's sensitivity to the syllable hierarchy is unlikely to result only from linguistic experience [similar results obtain in neonates (27) and in adult Korean speakers whose language lacks onset clusters altogether (4)]. …”
Section: Discussionmentioning
confidence: 79%
“…Across languages, certain syllable types (e.g., blog) are overrepresented relative to others (e.g., lbog), and preferred syllables are more readily identified by individual speakers-both adults (14,(16)(17)(18)(19)(20) and infants (27). However, whether such preferences Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that prenatal exposure to the maternal voice and heartbeat sounds can pave the neural pathways in the brain for subsequent development of hearing and language skills (14). For example, the periodic perception of the low-frequency maternal heartbeat in the womb provides the fetus with an important rhythmic experience (15,16) that likely establishes the neural basis for auditory entrainment and synchrony skills necessary for vocal, gestural, and gaze communication during mother-infant interactions (17,18).…”
mentioning
confidence: 99%